Peer Effects in Employment Status: Evidence from Housing Lotteries for Forced Evacuees in Fukushima - Ayako Kondo; Masahiro Shoji (Global Labor Organization (GLO), 2017)
Does a high peer employment rate increase individual employment probability? We exploit the random assignment of temporary housing to evacuees from the Fukushima Daiichi nuclear power plant accident to identify the effect of neighbors' employment rates on an individual's probability of finding a job post-evacuation. Using unique survey data, we find that a one standard deviation increase in the initial employment rate of an individual's peers makes the hazard of restarting work 1.41 times larger during the six months after move-in. We also show suggestive evidence for social norm to work as an underlying mechanism for the observed peer effect.
Keywords: 330